KAJIAN PEWARNA SECANG LIMBAH CAIR PEWARNAAN KULIT TERSAMAK TERHADAP UJI TOKSISITAS AKUT BENIH IKAN MAS (Cyprinus carpio L) - Entin Darmawati; Sudarmadji Sudarmadji; Umar Santoso (Politeknik ATK Yogyakarta, 2017)
The Research aims to know the exposure and acute 96-hour toxicity test of dye liquid waste (natural and synthetic) on chrom leather from sheep and cow crust towards goldfish seed. The materials used are dye liquid waste of secang (fermented and dried treatment) and synthetic (Acid Dyestuff); and goldfish seed (Cyprinus carpio L). The research has been done in 3 (three) phases: (1) Acclimatization, (2) Acute Toxicity Test LC50-96h, and (3) Probit Analysis Calculation. The data collected were the number of death of tested fish within 96 hours and then analyzed by using probit method (Probit Analysis). The result of the research shows that there are differences of toxic effects of liquid waste from secang and synthetic dyes. Secang dye has lower toxic effect category (slope value = 4.0, LC50-96hour=29.51%), with upper threshold value (N) of 32.0%. In lower threshold value (n) of 28.0% of this concentration, 50% animals tested died. Synthetic dyes had high toxic effect categories (slope value = 11,36, LC50-96hour =1.44%), with upper threshold value (N) of 4.0%. In lower threshold value (n) of 1.5.0% at this concentration tested animals, i.e. goldfish seed (Cyprinus carpio L), experienced 50% mortality on acute toxicity test (LC50 -96 hours). It can be concluded that secang dye is more environmentally friendly than synthetic ones, so it can be used as an alternative in the process of dyeing in the leather industry.